2014
DOI: 10.1111/jfb.12355
|View full text |Cite
|
Sign up to set email alerts
|

Multispecies spawning sites for fishes on a low‐latitude coral reef: spatial and temporal patterns

Abstract: Spawning sites used by one or more species were located by intensively searching nearshore coral reefs of Kimbe Bay (New Britain, Papua New Guinea). Once identified, the spawning sites were surveyed repeatedly within fixed 5 m radius circular areas, for > 2000 h of observations ranging from before dawn to after dusk spanning 190 days between July 2001 and May 2004. A total of 38 spawning sites were identified on the seven study reefs distributed at an average of one site every 60 m of reef edge. Pelagic spawni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(85 citation statements)
references
References 55 publications
0
84
1
Order By: Relevance
“…Ctenochaetus striatus) (Claydon et al, 2014) which were among the species contributing most to the observed differences between neap and spring tide samples. Spawning of these species commonly takes place at well-defined sites (Claydon et al, 2014), and migration from/to spawning sites could be a possible reason for the differing abundances of these species during neap tides. Due to their predictability in time and space spawning migrations also have direct consequences for fish catchability (Bos and Gumanao, 2012) and hence for conservation and management strategies of exploited stocks (Robinson et al, 2011).…”
Section: Lunar Cyclementioning
confidence: 92%
See 1 more Smart Citation
“…Ctenochaetus striatus) (Claydon et al, 2014) which were among the species contributing most to the observed differences between neap and spring tide samples. Spawning of these species commonly takes place at well-defined sites (Claydon et al, 2014), and migration from/to spawning sites could be a possible reason for the differing abundances of these species during neap tides. Due to their predictability in time and space spawning migrations also have direct consequences for fish catchability (Bos and Gumanao, 2012) and hence for conservation and management strategies of exploited stocks (Robinson et al, 2011).…”
Section: Lunar Cyclementioning
confidence: 92%
“…Chlorurus sordidus) or Acanthuridae (e.g. Ctenochaetus striatus) (Claydon et al, 2014) which were among the species contributing most to the observed differences between neap and spring tide samples. Spawning of these species commonly takes place at well-defined sites (Claydon et al, 2014), and migration from/to spawning sites could be a possible reason for the differing abundances of these species during neap tides.…”
Section: Lunar Cyclementioning
confidence: 92%
“…; Claydon et al . ) that gather in the same location at different times of the year according to specific seasonal, lunar, tidal and diel cycles. As one notable example, Kobara and Heyman () showed that all fourteen known Nassau grouper ( Epinephelus striatus , Epinephelidae) spawning sites in Belize harbour multispecies FSAs.…”
Section: Hotspots Of Marine Productivity That Support Ecosystem Healthmentioning
confidence: 99%
“…Therefore, FSAs are broadly meaningful across taxa and global geography despite being underdocumented. Many FSA sites harbour aggregations of several or even tens of species (Sedberry et al 2006;Heyman and Kjerfve 2008;Sadovy de Mitcheson et al 2008;Kobara et al 2013;Claydon et al 2014) that gather in the same location at different times of the year according to specific seasonal, lunar, tidal and diel cycles. As one notable example, Kobara and Heyman (2010) showed that all fourteen known Nassau grouper (Epinephelus striatus, Epinephelidae) spawning sites in Belize harbour multispecies FSAs.…”
Section: Hotspots Of Marine Productivity That Support Ecosystem Healthmentioning
confidence: 99%
“…Lunar periodicity in spawning and larval settlement back to reef habitat is common (Claydon et al. , Foster et al. , Shima et al.…”
Section: Introductionmentioning
confidence: 99%